Piezoelectric laminate and piezoelectric element

By using a first perovskite-type oxide piezoelectric film containing Nb and a second perovskite-type oxide seed layer matching thereto in the piezoelectric element, combining electron backscattering and diffraction method to control the crystal particle size distribution and optimize the polarization-electric field characteristics, the problem of difficult to take into account both piezoelectric performance and reliability in the prior art is solved, and efficient and reliable piezoelectric performance is achieved.

CN119630261APending Publication Date: 2025-03-14FUJIFILM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411255598.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-14
Filing Date
2024-09-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While improving piezoelectric properties, it is difficult to ensure the reliability of piezoelectric elements, especially when the seed layer is included.

Method used

A piezoelectric film containing the first perovskite oxide as the main component of Pb, Zr, Ti and Nb is used, and a seed layer with the second perovskite oxide as the main component of the lattice matching the first perovskite oxide is used to control the crystal particle size distribution through electron backscattering diffraction method, and the polarization-electric field characteristics are optimized to improve piezoelectric performance and reliability.

Benefits of technology

High voltage electrical performance and higher reliability are achieved, the risk of polarization reversal is reduced, voltage withstand voltage and durability are improved, power consumption is reduced, and the crystallinity and conductivity of the piezoelectric film are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630261A_ABST
    Figure CN119630261A_ABST
Patent Text Reader

Abstract

The invention provides a piezoelectric laminated body and a piezoelectric element. The piezoelectric laminated body has high piezoelectric performance and higher reliability compared with the prior art when provided with a seed layer. The piezoelectric laminate and the piezoelectric element are sequentially provided with a lower electrode layer, a seed crystal layer and a piezoelectric film on a substrate, the piezoelectric film is mainly composed of a first perovskite oxide containing Pb, Zr, Ti and Nb, and the seed crystal layer is mainly composed of a second perovskite oxide lattice-matched with the first perovskite oxide. The piezoelectric film has a proportion of crystal grains having a grain size of 100 nm or less in a crystal grain size distribution obtained by electron backscatter diffraction of 15% or less, and satisfies Ec + + Ec < Ec +-Ec-55 kV / cm < = Ec + < = 75 kV / cm, and 75 kV / cm < = Ec +-Ec < = 100 kV / cm, where Ec + is a positive-side coercive field and Ec-is a negative-side coercive field in polarization-electric field characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a piezoelectric laminate and a piezoelectric element. Background Art

[0002] As materials with excellent piezoelectric properties and ferroelectricity, perovskite oxides such as lead zirconate titanate (Pb(Zr, Ti)O3, hereinafter referred to as PZT) are known. Piezoelectric bodies composed of perovskite oxides are used as piezoelectric films in piezoelectric elements having a lower electrode, a piezoelectric film, and an upper electrode on a substrate. The piezoelectric element is used in various devices such as memory, inkjet head (actuator), micromirror device, angular velocity sensor, gyro sensor, ultrasonic element (PMUT: Piezoelectric Micromachined Ultrasonic Transducer) and vibration power generation device.

[0003] Patent documents 1 and 2 disclose that a piezoelectric film having high orientation and good piezoelectric performance can be realized by adding Nb (niobium) to the B position in a PZT-based perovskite oxide. Patent document 3 discloses that the piezoelectric performance of a piezoelectric film produced using a sol-gel method can be improved by adding Mn (manganese) in addition to Nb.

[0004] Patent document 1 states that in a piezoelectric film composed of PZT to which Nb is added, the grain size is distributed over a wide range, and the piezoelectric performance can be improved by mixing large-grained crystals with small-grained crystals. Specifically, it is stated that the grain size of 100 nm or less is preferably 20% or more, and the grain size of 500 nm or more is preferably 5% or more.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2009-71295

[0008] Patent Document 2: Japanese Patent Application Publication No. 2014-60330

[0009] Patent Document 3: International Publication No. 2015 / 146607

[0010] On the other hand, in order to improve the piezoelectric performance, it is known to provide a seed layer between the piezoelectric film and the lower electrode. However, in Patent Document 1, the case of providing a seed layer is not fully studied. Summary of the invention

[0011] The technology of the present invention has been accomplished in view of the above circumstances, and an object of the present invention is to provide a piezoelectric laminate and a piezoelectric element that have high piezoelectric performance and higher reliability than before when a seed layer is provided.

[0012] The piezoelectric laminate of the present invention is a piezoelectric laminate comprising a lower electrode layer, a seed layer, and a piezoelectric film in this order on a substrate, wherein:

[0013] The piezoelectric film is mainly composed of a first perovskite-type oxide containing Pb, Zr, Ti and Nb, the seed layer is mainly composed of a second perovskite-type oxide lattice-matched with the first perovskite-type oxide, the piezoelectric film has a grain size distribution obtained by an electron backscatter diffraction method, the proportion of grains with a grain size of less than 100 nm is less than 15%, and the positive side coercive field in the polarization-electric field characteristic is set to Ec + , set the negative side coercive field to Ec - Time Satisfaction

[0014] |Ec + +Ec - |<|Ec + -Ec - |

[0015] 55kV / cm≤Ec + ≤75kV / cm

[0016] 75kV / cm≤Ec + -Ec - ≤100kV / cm.

[0017] The piezoelectric film is preferably a sputtered film.

[0018] The proportion of crystal grains having a crystal grain size of 100 nm or less is preferably 10% or less.

[0019] Preferably, the first perovskite-type oxide is

[0020] Pb a {(Zr x Ti 1-x ) 1-y Nb y}O3,

[0021] Satisfies 0<x<1, 0.08≤y≤0.15, 0.9≤a≤1.2.

[0022] The seed layer is preferably conductive.

[0023] It is preferable that the lattice constant of the second perovskite type oxide when regarded as a pseudo-cubic crystal is 0.39 nm to 0.405 nm.

[0024] The second perovskite type oxide is preferably SrRuO 3 or BaRuO 3 .

[0025] The piezoelectric element of the present invention includes the piezoelectric stack of the present invention and an upper electrode layer provided on the piezoelectric film of the piezoelectric stack.

[0026] Effects of the Invention

[0027] According to the technology of the present invention, it is possible to provide a piezoelectric laminate and a piezoelectric element having high piezoelectric performance and higher reliability than before. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic cross-sectional view showing the layer structure of a piezoelectric stack and a piezoelectric element according to one embodiment.

[0029] Figure 2 It is a schematic diagram of a polarization-electric field (PE) hysteresis loop showing the PE characteristics of a piezoelectric element according to one embodiment.

[0030] Figure 3 PE hysteresis loops of Example 1 and Comparative Example 1 are shown.

[0031] Figure 4 This is an image pattern of crystal grains on the surface of the piezoelectric film of Example 1 obtained by the EBSD method.

[0032] Figure 5 This is the particle size distribution in the piezoelectric film of Example 1 obtained by the EBSD method.

[0033] Explanation of symbols

[0034] 1- piezoelectric element, 5- piezoelectric stack, 10- substrate, 12- lower electrode layer, 13- seed layer, 15- piezoelectric film, 18- upper electrode layer. DETAILED DESCRIPTION

[0035] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In addition, in the following drawings, for easy visual recognition, the layer thickness of each layer and their ratios are appropriately changed and depicted, which may not necessarily reflect the actual layer thickness and ratio. In this specification, the numerical range represented by "~" refers to the range including the numerical values ​​recorded before and after "~" as the lower limit and upper limit. In the numerical range recorded in stages in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of other numerical ranges recorded in stages. Moreover, in the numerical range recorded in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment.

[0036] Figure 1 1 is a schematic cross-sectional view showing the layer structure of a piezoelectric stack 5 and a piezoelectric element 1 including the piezoelectric stack 5 according to one embodiment. Figure 1 As shown, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10 and a lower electrode layer 12, a seed layer 13, and a piezoelectric film 15 stacked in sequence on the substrate 10. Here, "lower" and "upper" do not refer to up and down in the vertical direction, but the electrode arranged on the side of the substrate 10 with the piezoelectric film 15 interposed therebetween is called the lower electrode layer 12, and the electrode arranged on the side opposite to the substrate 10 with respect to the piezoelectric film 15 is called the upper electrode layer 18.

[0037] The substrate 10 is not particularly limited, and examples thereof include substrates such as silicon, glass, stainless steel, yttrium-stabilized zirconia, aluminum oxide, sapphire, and silicon carbide. As the substrate 10, a laminated substrate such as a silicon substrate with a thermal oxide film formed on the surface of a silicon substrate with a SiO2 oxide film can be used. In addition, as the substrate 10, a resin substrate such as PET (polyethyleneterephthalate), PEN (polyethylene naphthalate), and polyimide can be used.

[0038] The lower electrode layer 12 is paired with the upper electrode layer 18 and is an electrode for applying voltage to the piezoelectric film 15. There is no particular limitation on the main component of the lower electrode layer 12, and examples thereof include metals or metal oxides such as Au (gold), Pt (platinum), Ir (iridium), Ru (ruthenium), Ti (titanium), Mo (molybdenum), Ta (tantalum) and Al (aluminum), and combinations thereof. In addition, ITO (Indium Tin Oxide: indium tin oxide) and the like can also be used. The lower electrode layer 12 can be a single layer or a stacked structure consisting of multiple layers. When the lower electrode layer 12 is a stacked structure, it is also preferably set to a structure having a bonding layer such as Ti, TiW or ZrO2 on the substrate 10 side in addition to the conductive layer composed of the above-mentioned materials.

[0039] The thickness of the lower electrode layer 12 is not particularly limited, but is preferably about 50 nm to 300 nm in general, and more preferably 100 nm to 300 nm.

[0040] The upper electrode layer 18 is paired with the lower electrode layer 12 and is an electrode for applying voltage to the piezoelectric film 15. The main component of the upper electrode layer 18 is not particularly limited, and examples thereof include metals such as Au, Pt, Ir, Ru, Ti, Mo, Ta and Al, or metal oxides thereof, and combinations thereof. In addition, ITO (Indium Tin Oxide), LaNiO3 and SrRuO3, etc., can be used. The upper electrode layer 18 can be a single layer or a stacked structure consisting of multiple layers. In addition, from the viewpoint of further suppressing the diffusion of oxygen from the piezoelectric film 15, at least the region of the upper electrode layer 18 that is in contact with the piezoelectric film 15 is preferably an oxide electrode.

[0041] The thickness of the upper electrode layer 18 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm.

[0042] The piezoelectric film 15 is mainly composed of a first perovskite oxide containing Pb, Zr, Ti and Nb. In this specification, the main component refers to a component that occupies 80 mol% or more. The piezoelectric film 15 is preferably composed of 90 mol% or more of the first perovskite oxide, and the piezoelectric film 15 is more preferably composed of 100 mol% of the first perovskite oxide (but including inevitable impurities).

[0043] The first perovskite type oxide containing Pb, Zr, Ti, and Nb, that is, PZT to which Nb is added is represented by the following general formula.

[0044] Pb a {(Zr x Ti 1-x ) 1-y Nb y}O3

[0045] Here, preferably, 0<x<1, 0<y<1, 0.9≤a≤1.2, and more preferably, 0.08≤y≤0.15.

[0046] Furthermore, when the piezoelectric film 15 is formed as a sputtered film formed by a vapor phase growth method such as sputtering, a piezoelectric film having a very high piezoelectric constant can be obtained.

[0047] In addition, it is believed that in PZT-based perovskite oxides, piezoelectric properties are shown at the morphotropic phase boundary (MPB) and its vicinity. The MPB composition is near Zr:Ti (molar ratio) = 52:48, and in the above general formula, it is preferably the MPB composition or its vicinity. "MPB or its vicinity" is the region where a phase change occurs when an electric field is applied to the piezoelectric film. Specifically, Zr:Ti (molar ratio) is preferably in the range of 45:55 to 55:45, that is, in the range of x = 0.45 to 0.55.

[0048] The film thickness of the piezoelectric film 15 is preferably not less than 0.2 μm and not more than 5 μm, and more preferably not less than 1 μm.

[0049] In the piezoelectric film 15, in the crystal grain size distribution obtained by the electron beam backscatter diffraction (EBSD) method, the proportion of grains with a grain size of 100 nm or less is 15% or less. In addition, the proportion of grains with a grain size of 100 nm or less is preferably 10% or less. The average grain size is preferably 200 nm or more, and the average grain size is more preferably 500 nm or more.

[0050] The seed layer 13 contains as a main component a second perovskite type oxide that is lattice matched with the first perovskite type oxide. The second perovskite type oxide is a perovskite type oxide having a composition different from that of the first perovskite type oxide.

[0051] The crystallinity of the piezoelectric film 15 formed on the upper layer can be improved by providing the seed layer 13. The piezoelectric film 15 formed on the seed layer 13 may also become an epitaxial film by epitaxial growth.

[0052] The second perovskite oxide preferably has a lattice constant of 0.39 nm to 0.405 nm when regarded as a pseudo-cubic crystal. When the lattice constant is within this range, it lattice-matches with the first perovskite oxide of PZT doped with Nb, thereby improving the crystallinity of the piezoelectric film 15 formed on the upper layer.

[0053] The seed layer 13 preferably has electrical conductivity. Electrical conductivity refers to a resistivity that allows the layer to function as an electrode. Here, the resistivity at 20° C. is 10 -5 When the conductivity is Ω·m or less, it is considered to have conductivity. As long as the seed layer 13 has conductivity, it can function as an electrode for applying a driving voltage to the piezoelectric film 15 together with the lower electrode layer 12 .

[0054] Specific examples of the second perovskite oxide include SrRuO3, BaRuO3, and PbTiO3. The lattice constants of these oxides when regarded as pseudo-cubic crystals are 0.39 nm to 0.405 nm. As the second perovskite oxide, SrRuO3 or BaRuO3 having conductivity is particularly preferred.

[0055] Figure 2It is a schematic diagram showing a PE hysteresis loop showing polarization-electric field (PE) characteristics obtained by grounding the lower electrode layer 12, using the upper electrode layer 18 as a driving electrode, and applying a scanning voltage to the piezoelectric film 15. In the PE hysteresis loop, when a positive potential is given to the upper electrode layer 18, it is represented as a positive voltage, and when a negative potential is given to the upper electrode layer 18, it is represented as a negative voltage. Since the first cycle of the measurement is affected by the polarization state before the measurement, the data sometimes become unstable, but a stable curve with roughly the same behavior can be obtained after about the second cycle. In the coercive field evaluation of the piezoelectric film, a stable PE hysteresis loop is used. For example, the data of the third cycle is used.

[0056] like Figure 2 As shown, the positive side coercive field is set to Ec + , set the negative side coercive field to Ec - When the piezoelectric film 15 satisfies

[0057] |Ec + +Ec - |<|Ec + -Ec - |

[0058] 55kV / cm≤Ec + ≤75kV / cm

[0059] 75kV / cm≤Ec + -Ec - ≤100kV / cm.

[0060] The coercive field refers to the electric field that polarizes to zero in the PE hysteresis loop, such as Figure 2 As shown, there are two coercive fields in a hysteresis loop. + It refers to the coercive field on the positive electric field side (right side in the figure) of the two coercive fields, and the negative coercive field Ec - It refers to the coercive field on the negative electric field side (left side in the figure).

[0061] In addition, Figure 2 In the PE hysteresis loop shown, the coercive field difference Ec + -Ec - The absolute value of represents the hysteresis width. Half of the sum of the coercive fields (Ec + +Ec - ) / 2 represents the hysteresis center H0. The displacement of the hysteresis center H0 from the origin indicates that the piezoelectric film 15 has spontaneous polarization. Furthermore, the displacement of the hysteresis center H0 to the positive electric field side indicates that spontaneous polarization occurs in the direction opposite to the direction of the electric field when a positive voltage is applied.

[0062] |Ec + -Ec -| is the absolute value of the coercive field difference, which, as mentioned above, represents the width of the hysteresis loop. And, as mentioned above, the center of the hysteresis loop is given by (Ec + +Ec - ) / 2. Therefore, (Ec + +Ec - ) / 2 represents the displacement of the hysteresis loop.

[0063] Above |Ec + +Ec - |<|Ec + -Ec - The relationship between | and |Ec + +Ec - | / 2<|Ec + -Ec - | / 2 has the same meaning, indicating that the displacement of the hysteresis loop is less than half of the hysteresis width, that is, the hysteresis loop contains the origin.

[0064] Usually, the spontaneous polarization of the PZT added with Nb is from the substrate side to the upper side of the film thickness direction just after the film is formed. Therefore, in a piezoelectric device having a PZT film added with Nb, the direction of the spontaneous polarization of the PZT film added with Nb is usually driven in the same direction as the direction of the electric field. Therefore, in a piezoelectric device having a PZT film added with Nb in the past, the upper electrode layer 18 is usually used as a driving electrode to perform negative voltage drive. However, as described above, the piezoelectric film 15 of the present embodiment includes an origin as a hysteresis loop of the PZT film added with Nb and the width of the hysteresis loop is large. This means that it can be polarized in a direction opposite to the direction of the spontaneous polarization just after the film is formed. By polarizing in a direction opposite to the direction of the spontaneous polarization just after the film is formed, when the upper electrode layer 18 is used as a driving electrode, positive voltage drive can be performed. The price of a positive voltage-driven driver is lower than that of a negative voltage-driven driver, which helps to suppress the cost of piezoelectric devices.

[0065] As described above, the piezoelectric stack 5 and the piezoelectric element 1 of the present embodiment include a seed layer 13 mainly composed of a second perovskite-type oxide between a piezoelectric film 15 mainly composed of a first perovskite-type oxide containing Pb, Zr, Ti, and Nb and a lower electrode layer 12, and the proportion of grains of the piezoelectric film 15 with a grain size of 100 nm or less obtained by electron backscatter diffraction is 15% or less. In addition, the positive side coercive field in the polarization-electric field characteristic is set to Ec + , set the negative side coercive field to Ec - When , the piezoelectric film 15 satisfies the above relationship.

[0066] The present inventors have found that the piezoelectric performance and reliability of the piezoelectric film can be improved by using such a structure (see Examples described below).

[0067] As mentioned above, |Ec + -Ec - | corresponds to the hysteresis width. The larger the hysteresis width, the more stable the piezoelectric film is that is less likely to undergo polarization reversal. On the other hand, if |Ec + -Ec - If the voltage is too large, it will be difficult to make the polarization uniform, so the piezoelectric performance will be reduced when the polarization is released. The coercive field is preferably less than the driving voltage. The piezoelectric film 15 of this embodiment satisfies 55 kV / cm≤Ec + ≤75kV / cm、75kV / cm≤Ec + -Ec - ≤100kV / cm, so stable and high reliability can be achieved. In addition, since the hysteresis loop includes the origin, polarization reversal does not occur during driving, which can suppress power consumption and contribute to long-term reliability.

[0068] By providing the seed layer 13, a piezoelectric film 15 with good lattice matching is grown, so the stress applied to the piezoelectric film can be suppressed compared to the case where the seed layer 13 is not provided. By suppressing the stress of the piezoelectric film 15, the withstand voltage and durability can be improved, and high reliability can be obtained. In Patent Document 1, stress relaxation is achieved by not having a seed layer 13 and including a large number of grains with small grain sizes in the piezoelectric film, but by providing the seed layer 13, stress can be suppressed even if grains with small grain sizes are not included. The inventors of the present invention have found that when the seed layer 13 is provided, the piezoelectric performance and reliability can be improved by suppressing small grains with a grain size of less than 100 nm. Insulation breakdown often occurs at grain boundaries. By suppressing grains with small grain sizes, the number of grain boundaries can be suppressed, so it is believed that this helps to improve withstand voltage and durability.

[0069] In addition, when a film is formed on the seed layer 13 by sputtering, the film formation is temporarily stopped at the stage of forming a very thin film in the early stage of film formation, specifically, at the stage of forming a film with a film thickness of less than 100 nm, and an annealing treatment is performed at a high temperature of 600° C. to 700° C., and then the film is formed to a set film thickness (for example, 2 μm), thereby obtaining the above-mentioned piezoelectric film 15. It is believed that this is because the annealing treatment promotes the crystal growth of PZT to which Nb is added, and the number of small-diameter grains can be reduced.

[0070] The piezoelectric element 1 or the piezoelectric laminate 5 according to each of the above-described embodiments can be suitably used in ultrasonic devices, mirror devices, sensors, memories, and the like.

[0071] Example

[0072] The following describes specific examples and comparative examples of the piezoelectric element of the present invention. First, the method for making the piezoelectric element of each example is described. A sputtering device is used in the film formation of each layer. In the description of the production method, reference is made to Figure 1 The piezoelectric element 1 will be described with reference to the symbols of the layers shown.

[0073] (Production Method)

[0074] As the substrate 10 , a silicon substrate with a thermal oxide film was used.

[0075] A substrate with an electrode layer was prepared in which a 20 nm thick adhesion layer composed of Ti, a 150 nm thick lower electrode layer 12 composed of Ir, and a 20 nm thick seed layer 13 composed of SrRuO3 (SRO in Table 1) were sequentially stacked on a thermal oxide film of a substrate 10. In addition, for Comparative Examples 1 and 3, a substrate with an electrode layer was prepared in which a 20 nm thick adhesion layer composed of Ti and a 150 nm thick lower electrode layer 12 composed of Ir were sequentially stacked on a thermal oxide film of the substrate 10 without a seed layer.

[0076] <Piezoelectric film>

[0077] On the seed layer 13, a PZT film with Nb added was formed as a piezoelectric film 15 under the following sputtering conditions. In addition, the film formation was temporarily interrupted at the initial stage of film formation, and annealing treatment was performed, and finally a 2μm thick PZT film with Nb added was formed. A PZT target with Nb added was used in the film formation. A target material set to a Pb composition ratio of 1.3, a Zr / Ti molar ratio of MPB composition (Zr / Ti=52 / 48), i.e., x=0.52, and a Nb composition ratio y=0.12 was used. The substrate temperature during film formation was set to 550°C.

[0078] -Sputtering conditions of piezoelectric film-

[0079] Distance between target and substrate: 100mm

[0080] Target input power: 3kW

[0081] Vacuum degree (film forming pressure): 0.5Pa

[0082] Atmosphere: Ar / O2 mixture (O2 volume fraction 2.5%)

[0083] Substrate setting temperature: 550℃

[0084] Substrate bias voltage: +40V

[0085] - Annealing conditions -

[0086] The conditions for temporarily stopping the film formation process and performing the annealing treatment are listed in Table 1. For example, in the case of Example 1, after forming a 30nm thick Nb-added PZT film as the initial piezoelectric film, the annealing treatment was performed at a temperature of 650°C for 10 minutes. The annealing treatment was performed in a state where the film formation was stopped in the film formation device and the temperature was only increased in a vacuum. In addition, in the case of Comparative Examples 1 and 2, the film formation process was not stopped, that is, the 2μm piezoelectric film was directly formed without annealing.

[0087] <Upper electrode layer>

[0088] An ITO layer having a thickness of 100 nm was formed as an upper electrode layer 18 on the piezoelectric film 15 of the above-mentioned laminated substrate by sputtering.

[0089] <Evaluation electrode pattern formation>

[0090] Before forming the upper electrode layer 18, a resist pattern was formed by photolithography, the upper electrode layer 18 was formed on the resist pattern, and an upper electrode pattern for evaluation was formed by lift-off.

[0091] Table 1 summarizes the seed layer, the thickness of the piezoelectric film before annealing (initial piezoelectric film thickness), and the temperature and time of the annealing for each of the comparative examples and examples.

[0092] [Table 1]

[0093]

[0094] (Preparation of samples for evaluation)

[0095] -Evaluation Sample 1-

[0096] A strip-shaped portion of 2 mm×25 mm was cut out from the laminate to prepare a cantilever as a sample 1 for evaluation.

[0097] -Evaluation Sample 2-

[0098] A 25 mm×25 mm portion having an upper electrode layer 18 patterned into a circle with a diameter of 400 μm at the center of the surface of the piezoelectric film 15 was cut out from the laminate as a sample 2 for evaluation.

[0099] <Measurement of polarization-electric field characteristics>

[0100] Regarding the piezoelectric elements of each embodiment and comparative example, the polarization-electric field (PE) hysteresis loop was measured using the evaluation sample 2. The ferroelectric property evaluation system FEC10 manufactured by TOYO Corporation was used in the measurement. For the piezoelectric elements of each embodiment and comparative example, the lower electrode layer 12 was grounded, and the driving voltage applied to the upper electrode layer 18 was changed from 0V=>+40V=>-40V=>0V with a 10Hz triangle wave, and the change in polarization value at this time was obtained. In addition, regarding the measurement of the hysteresis loop, the change from 0V=>+40V=>-40V=>0V was regarded as one cycle, and the coercive field value was determined based on the data of the third cycle. As described above, when measuring the hysteresis loop, the first cycle is unstable, and a stable hysteresis loop with roughly the same behavior can be obtained after about the second cycle. Here, for the sake of caution, the data of the third cycle is used. Figure 3 The PE hysteresis loops of Example 1 and Comparative Example 1 are shown. The horizontal axis represents the electric field calculated by dividing the applied voltage by the thickness of 2 μm.

[0101] like Figure 3 As shown, in the hysteresis loop of Example 1, the positive side coercive field Ec + The negative coercive field Ec is 66kV / cm. - is -27kV / cm. Therefore, |Ec + +Ec - | is 39kV / cm, |Ec + -Ec - The coercive fields of other embodiments and comparative examples are shown in Table 2.

[0102] <Measurement of piezoelectric constant>

[0103] The piezoelectric constant d was measured using a cantilever according to the method described in I. Kanno et al. Sensor and Actuator A 107 (2003) 68., using a +10V±10V sine wave applied voltage, that is, a +10V bias voltage and a 10V amplitude sine wave applied voltage. 31 [pm / V] Before measuring the piezoelectric constant, a polarization treatment was performed by applying +40 V for 10 seconds. The measurement results are shown in Table 2.

[0104] The piezoelectric constant was evaluated according to the following criteria, and the evaluation results are shown in Table 2.

[0105] A: 200pm / V or more

[0106] B: 170pm / V or more and less than 200pm / V

[0107] C: less than 170pm / V

[0108] <Evaluation of withstand voltage>

[0109] The withstand voltage (insulation breakdown voltage) of each embodiment and comparative example was measured. Using the evaluation sample 2, the lower electrode layer 12 was grounded, and a positive voltage was applied to the upper electrode layer 18 at a rate of change of +1V / sec. The voltage at which a current of 1mA or more flowed was regarded as the withstand voltage. Ten samples were prepared for each example, and a total of 10 measurements were performed, and the average value was expressed as the withstand voltage [V] in Table 2.

[0110] The withstand voltage was evaluated according to the following criteria, and the evaluation results are shown in Table 2.

[0111] A: 150V or above

[0112] B: 100V or more and less than 150V

[0113] C: less than 100V

[0114] <Evaluation of driving stability (reliability)>

[0115] As an evaluation of the driving stability of each embodiment and comparative example, a time-dependent dielectric breakdown (TDDB) test was performed. Using evaluation sample 2, the lower electrode layer 12 was grounded in an environment of 120°C, a voltage of +40V was applied to the upper electrode layer 18, and the time (hr) from the start of voltage application until dielectric breakdown occurred was measured. The measurement results are shown in Table 2. In addition, the TDDB test was performed for 2000 hours, and when dielectric breakdown did not occur within 2000 hours, it was recorded as 2000 in Table 2.

[0116] The reliability was evaluated according to the following criteria, and the evaluation results are shown in Table 2.

[0117] A: 1500hr or more

[0118] B: 1000hr or more and less than 1500hr

[0119] C: less than 1000hr

[0120] <Method for measuring crystal particle size>

[0121] The surface of the piezoelectric film after formation, i.e., the surface of the piezoelectric film before the upper electrode was formed, was measured by EBSD. As the measuring apparatus, a SEM (Scanning Electron Microscope): JSM-7001F manufactured by JEOL Ltd. and an EBSD OIM manufactured by TSL were used. The image pattern of the crystal grains on the surface of the piezoelectric film of Example 1 obtained by the EBSD method is shown in FIG. Figure 4 .like Figure 4 As shown in the enlarged view in , the crystal grains are identified and the diameter of the smallest circumscribed circle is calculated as the crystal grain size. Figure 5 Shown from Figure 4 Obtained particle size distribution. Figure 5 In the figure, ~0.1 on the horizontal axis indicates 0.1 μm or less (100 nm or less), ~0.2 indicates more than 0.1 μm and less than 0.2 μm, and ~0.3 indicates more than 0.2 μm and less than 0.3 μm. The same applies to ~0.4 and above. Figure 5 As shown, in Example 1, the crystal grains with a grain size of 100 nm or less account for 10% of all the crystal grains in the field of view. Table 2 shows the proportion of crystal grains with a grain size of 100 nm or less in each of the Examples and Comparative Examples.

[0122] In addition, for each of the examples and comparative examples, the lowest evaluation results in each of the evaluations of the piezoelectric constant, the withstand voltage, and the reliability are respectively described in Table 2 as a comprehensive evaluation.

[0123]

[0124] From the results of Comparative Examples 1 and 3, it can be seen that the result of Comparative Example 1 in which the ratio of grains with a grain size of 100 nm or less exceeded 30% when there was no seed layer showed high piezoelectric constant, withstand voltage and reliability.

[0125] In Examples 1 to 5, all evaluations were B or higher, and good results were obtained in piezoelectric constant, withstand voltage and reliability. Examples 1 to 5 and Comparative Example 2 satisfied the following. Comparative Example 1 and Comparative Example 3 did not satisfy at least one of the following formulas.

[0126] |Ec + +Ec - |<|Ec + -Ec - |

[0127] 55kV / cm≤Ec + ≤75kV / cm

[0128] 75kV / cm≤Ec + -Ec - ≤100kV / cm

[0129] Furthermore, the proportion of crystal grains having a grain size of 100 nm or less was 15% or less in Examples 1 to 5. It is understood that by satisfying these ranges, good piezoelectric constants, withstand voltages, and reliability can be obtained.

[0130] The withstand voltage and reliability of Example 3 are evaluated lower than those of Examples 1, 2, 4, and 5. Based on this result, it is considered that the proportion of grains with a grain size of 100 nm or less in the piezoelectric film 15 is more preferably 10% or less. In addition, in Comparative Example 2, in which the proportion of grains with a grain size of 100 nm or less is as high as 35% when a seed layer is provided, the piezoelectric constant is good, but the withstand voltage and reliability are lower than those of Examples 1 to 5, which shows the effect obtained by reducing the proportion of grains with a grain size of 100 nm or less.

[0131] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical standard were specifically and individually described as being incorporated by reference.

[0132] The following additional notes are further disclosed regarding the above-mentioned embodiment.

[0133] <Note 1>

[0134] 1. A piezoelectric laminate, comprising a lower electrode layer, a seed layer and a piezoelectric film in this order on a substrate, wherein:

[0135] The piezoelectric film is mainly composed of a first perovskite-type oxide containing Pb, Zr, Ti and Nb.

[0136] The seed layer is mainly composed of a second perovskite-type oxide that is lattice-matched with the first perovskite-type oxide.

[0137] The piezoelectric film has a crystal grain size distribution obtained by electron backscatter diffraction method, in which the proportion of grains with a grain size of 100 nm or less is 15% or less, and a positive coercive field in the polarization-electric field characteristic is set to Ec + , set the negative side coercive field to Ec - Time Satisfaction

[0138] |Ec + +Ec - |<|Ec + -Ec - |

[0139] 55kV / cm≤Ec + ≤75kV / cm

[0140] 75kV / cm≤Ec + -Ec - ≤100kV / cm.

[0141] <Note 2>

[0142] The piezoelectric stack according to Supplementary Note 1, wherein

[0143] The piezoelectric film is a sputtered film.

[0144] <Note 3>

[0145] The piezoelectric stack according to Supplement 1 or Supplement 2, wherein

[0146] The crystal grains having a particle size of 100 nm or less account for less than 10%.

[0147] <Note 4>

[0148] The piezoelectric stack according to any one of Supplementary Notes 1 to 3, wherein

[0149] The first perovskite oxide is Pb a {(Zr x Ti 1-x ) 1-y Nb y}O3,

[0150] Satisfies 0<x<1, 0.08≤y≤0.15, 0.9≤a≤1.2.

[0151] <Note 5>

[0152] The piezoelectric stack according to any one of Supplementary Notes 1 to 4, wherein

[0153] The seed layer has conductivity.

[0154] <Note 6>

[0155] The piezoelectric stack according to any one of Supplementary Notes 1 to 5, wherein

[0156] The lattice constant of the second perovskite type oxide when regarded as a pseudo-cubic crystal is 0.39 nm to 0.405 nm.

[0157] <Note 7>

[0158] The piezoelectric stack according to any one of Supplementary Notes 1 to 6, wherein

[0159] The second perovskite-type oxide is SrRuO3 or BaRuO3.

[0160] <Note 8>

[0161] A piezoelectric element comprising:

[0162] The piezoelectric stack according to any one of Supplementary Notes 1 to 7; and

[0163] An upper electrode layer is provided on the piezoelectric film of the piezoelectric stack.

Claims

1. A piezoelectric laminate, comprising a lower electrode layer, a seed layer and a piezoelectric film in this order on a substrate, wherein: The piezoelectric film is mainly composed of a first perovskite-type oxide containing Pb, Zr, Ti and Nb. The seed layer is mainly composed of a second perovskite-type oxide that is lattice-matched with the first perovskite-type oxide. The piezoelectric film has a crystal grain size distribution obtained by electron backscatter diffraction method, in which the proportion of grains with a grain size of less than 100 nm is less than 15%, and a positive coercive field in the polarization-electric field characteristic is denoted as Ec + , assuming the negative side coercive field is Ec - Time Satisfaction |Ec + +Ec - |<|Ec + -Ec - | 55kV / cm≤Ec + ≤75kV / cm 75kV / cm≤Ec + -Ec - ≤100kV / cm。 2. The piezoelectric stack according to claim 1, wherein The piezoelectric film is a sputtered film.

3. The piezoelectric stack according to claim 1 or 2, wherein: The crystal grains having a particle size of 100 nm or less account for less than 10%.

4. The piezoelectric stack according to claim 1 or 2, wherein: The first perovskite oxide is Pb a {(Zr x Ti 1-x ) 1-y Nb y }O3, Satisfies 0<x<1, 0.08≤y≤0.15, 0.9≤a≤1.

2.

5. The piezoelectric laminate according to claim 1 or 2, wherein: The seed layer has conductivity.

6. The piezoelectric laminate according to claim 1 or 2, wherein: The lattice constant of the second perovskite type oxide when regarded as a pseudo-cubic crystal is 0.39 nm to 0.405 nm.

7. The piezoelectric stack according to claim 1 or 2, wherein: The second perovskite-type oxide is SrRuO3 or BaRuO3.

8. A piezoelectric element comprising: The piezoelectric stack according to any one of claims 1 to 7; and An upper electrode layer is provided on the piezoelectric film of the piezoelectric stack.

Citation Information

Patent Citations

  • Piezoelectric device and liquid discharge apparatus using the same

    JP2009071295A

  • Piezoelectric device and using method thereof

    JP2014060330A

  • Composition for forming manganese- and niobium-doped PZT piezoelectric film

    WO2015146607A1